Maintaining The Sustainable Engagement of Adolescent in Family Team of Stunting Prevention Program - La Jumu; Isak Jurun Hans Tukayo; Sukatemin Sukatemin; Syaifoel Hardy (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Maintaining the sustainable engagement of youth as part of the Family Assistance Team (TPK) in the Family Planning (KB) program is needed. The objective is to provide a structured framework on how to recruit youth to the Family Assistance Team (TPK). This study used a qualitative method with a descriptive design. The instrument used was a list of semi-structured questions. The participants were 3 nurses, a midwife, and one family planning instructor (PKB). Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The supporting tool was Appreciative Inquiry (AI). The results were based on the AI analysis it was found there were five important components considered as determining aspects in maintaining the sustainability of youth in stunting prevention program (i.e recruitment requirements, training programs, parental permission, willingness of youth, and incentives). We recommended that knowledge; skills, parents’ permission, motivation, and those currently studying health majors should be considered as they have the potential to maintain the sustainability of their engagement in the stunting reduction program. Abstrack: Mempertahankan keterlibatan pemuda yang berkelanjutan sebagai bagian dari Tim Pendamping Keluarga (TPK) dalam program Keluarga Berencana (KB) sangat diperlukan. Tujuannya adalah untuk memberikan kerangka terstruktur tentang cara merekrut pemuda ke dalam Tim Pendamping Keluarga (TPK). Metode Penelitian ini kualitatif dengan desain deskriptif. Instrumen yang digunakan adalah daftar pertanyaan semi terstruktur. Peserta terdiri dari 3 orang perawat, seorang bidan, dan satu orang penyuluh Keluarga Berencana (PKB). Data dikumpulkan melalui proses wawancara mendalam dan dianalisis menggunakan teknik analisis tematik. Alat pendukungnya adalah Appreciative Inquiry (AI). Berdasarkan analisis AI ditemukan ada lima komponen penting yang dianggap sebagai aspek penentu dalam menjaga keberlanjutan remaja dalam TPK guna pencegahan stunting (yakni persyaratan, program pelatihan, izin orang tua, kemauan remaja, dan insentif). Kesimpulannya kami merekomendasikan pengetahuan; keterampilan, izin orang tua, motivasi, dan mereka yang sedang menempuh pendidikan di jurusan kesehatan perlu dipertimbangkan karena berpotensi mampu mempertahankan berlangsungnya keterlibatannya mereka dalam program pencegahan stunting.